2001
DOI: 10.1590/s0103-90162001000100013
|View full text |Cite
|
Sign up to set email alerts
|

Concentração de bap e a eficiência de micropropagação de bananeira tetraplóide (grupo AAAB)

Abstract: Com o objetivo de desenvolver um procedimento eficiente para a produção de mudas de bananeiras tetraplóides (Musa sp. cv. FHIA-01, grupo AAAB) estudou-se o efeito do clone no desenvolvimento in vitro dos explantes e as taxas de contaminação, multiplicação e nível de oxidação em meios de cultura contendo cinco concentrações de BAP. Na fase de introdução in vitro dos explantes, foi observada elevada taxa de contaminação (22,32%), causada, principalmente, por bactérias. No entanto, os níveis de contaminação decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
5
0
12
Order By: Relevance
“…For the height characteristic (H) shown in Figure 2B, there was a quadratic effect where height increased according to the increase in BAP concentration to the concentration of 8.71 μmol L -1 , with a maximum height of 32.70 mm; from this concentration, there was a fall in plant height. Oliveira et al (2001), studying banana tree cultivar FHIA-01 (Musa sp., AAAB Group), in which the height of the seedlings during multiplication was inversely proportional to the BAP concentration, observed that the seedlings obtained in the BAP concentrations of 5.0 mg.L -1 and especially of 7.5 mg.L -1 presented a reduced size, always inferior to 1.5 cm. The inhibitory effect of BAP on shoot height was also reported in the in vitro of the "macela" (DINIZ et al, 2003), of vine (LUCAS et al, 2006), of Prunaceas (LEONTIEV-ORLOV et al, 2000) and peach trees (ROGALSKI, 2002).…”
Section: • Analysis At 30 Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…For the height characteristic (H) shown in Figure 2B, there was a quadratic effect where height increased according to the increase in BAP concentration to the concentration of 8.71 μmol L -1 , with a maximum height of 32.70 mm; from this concentration, there was a fall in plant height. Oliveira et al (2001), studying banana tree cultivar FHIA-01 (Musa sp., AAAB Group), in which the height of the seedlings during multiplication was inversely proportional to the BAP concentration, observed that the seedlings obtained in the BAP concentrations of 5.0 mg.L -1 and especially of 7.5 mg.L -1 presented a reduced size, always inferior to 1.5 cm. The inhibitory effect of BAP on shoot height was also reported in the in vitro of the "macela" (DINIZ et al, 2003), of vine (LUCAS et al, 2006), of Prunaceas (LEONTIEV-ORLOV et al, 2000) and peach trees (ROGALSKI, 2002).…”
Section: • Analysis At 30 Daysmentioning
confidence: 99%
“…According to Oliveira et al (2001), these small seedlings are not desirable in the micropropagation process because they need to undergo an elongation before rooting, so that there are no high losses in acclimatization As at 30 days, the 60-day analysis showed that the increase in BAP concentrations positively influenced the characteristics evaluated up to a certain concentration, from which there was an opposite effect, which can be explained by the endogenous level of cytokinin in the microshoots, causing excessive high concentrations to the plants in vitro.…”
Section: • Analysis At 30 Daysmentioning
confidence: 99%
“…However, at the same time, the shoots were of a shorter length. This contradictory behavior is explained by the fact that the exacerbated increase in the number of shoots would have promoted competition for the salts and vitamins in the culture medium, thus reducing growth (OLIVEIRA et al, 2001).…”
Section: +mentioning
confidence: 99%
“…Outros trabalhos têm utilizado diluições de sais minerais nos meios de cultura em diversas frutíferas, tais como maçã (Pasqual et al, 2000), maracujá (Biasi et al, 2000), banana (Oliveira et al, 2001) e citros , com resultados positivos no enraizamento.…”
Section: Comprimento Do Explante (Cm) Explantes Responsivos (%)unclassified